The Law of Polygamy in Islam: a Methodological Review of Siti Musdah Mulia’s Legal Thought - Y Yusefri (Institut Agama Islam Negeri (IAIN) Curup, 2017)
This essay essentially conducts an objective and critical review of how the constructs and methodological frameworks of Siti Musdah Mulia thought that concluded that polygamy law is haram lighairihi. Some of the main points to be analyzed in relation to this study are the approach which used by her and her method of seeing the verses on polygamy, the polygamy fair terms, the practice of the Prophet's polygamy, and her conception of the lighairihi haram. This study is character studies form, and the primary data material is the works of Siti Musdah Mulia through by using literature study. The analytical method used analysis content with a normative approach. This study found that in carrying out her thoughts on the unlawful law of polygamy lighairihi, Siti Musdah Mulia used several kinds of arguments: normative argumentation, in the form of Qur'an and hadith, jurisprudence and empirical social facts. While in understanding the verses and traditions concerning polygamy, it is more likely use contextual approach and analysis, maqâshid al-syarî'ah (philosophical), socio-historical.